Pricing and efficient public transport supply in a mobility as a service context - Daniel Hörcher; Daniel J. Graham (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
Mobility as a Service (MaaS) is widely expected to make sustainable transport choices more attractive. New approaches to ticketing will be a core part of MaaS, both to attract users and fund services. The associated pricing decisions will be a matter of public policy as much as business objectives, because they can have large social welfare effects. This paper describes options for different pricing structures and their relative efficiency. It considers the potential impact that differing objectives of public and privately-owned transport providers might have on pricing decisions. It concludes with an assessment of the possible effects of Covid-19 on the MaaS market.
Keywords: 330; Öffentlicher Verkehr; Mobilität; Dienstleistungsqualität; Coronavirus